IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KELUARGA SAKINAH PERSPEKTIF QURAISH SHIHAB - Mohammad Alfian Nur Rosyid; Ahmad Zahro (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2020)
Islam forbids a form of marriage which only aims temporarily, such as mut’ah marriage and muhalil marriage For that the need for planting Islamic religious education values in shaping the sakinah family of Quraish Shihab's perspective. This thesis is qualitative research (Library research). Data was collected by documentation, then the data was analyzed by Descriptive methods. According to the Quraish Shihab there is an important aspect that aims for a family to go to a sakinah family, namely by paying attention to things in the family which include leadership, and knowing the task - tasks from mother, father and child so that they can be affectionate, have each other so that they can create a feeling of calm so that they know how the functions that exist in a family. This concept aims at the couple and wife working together in fostering the household to make the family happy.